Uji Aktivitas Penghambatan Enzim A-Glukosidase Daun Kalanchoe Pinnata Pers - Efizal, Efizal; Soemiati, Atiek; Hanafi, M; Dwiyanti, Indah (Majalah Ilmu Kefarmasian, 2007)
The study of inhibitory activity against the a-glucosidase enzyme of Kalanchoe pinnata Pers. leaves has been carried out. In vitro, the methanol extract, n-hexane fraction, ethyl acetate fraction and methanol-water (1:1) fraction inhibited a-glucosidase enzyme activities with IC50 value 72.8, 982.6, 194.6 and 293.8 ug/mL, respectively. In vivo, the study was conducted in normal ddY mice by using oral glucose tolerance test. The administration of methanol extract dose 0.5, 1.0 g/kg of body weight and ethyl acetate fraction dose 1.0 g/kg of body weight can suppress the blood glucose level at 30 min significantly (p<0.05) if compared with control after oral administration of sucrose (3 g/kg of body weight), and their activity were similar with acarbose 0.01 g/kg of body weight (p>0.05).